Access Clean Water in The Community of Surabaya City and Their Bad Impacts Clean Water Access to Surabaya Community Productivity - Triono, Mohammad Oni (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2018)
This research was conducted to see how access to clean water in the people of Surabaya and the impact of poor access to clean water on productivity. 70% of Surabaya's community water sources come from PDAM water, while the rest comes from ground water through wells, but in the poor only 54% use tap water. Poor access to clean water can cause illness, especially diarrhea. With the Two Way ANOVA analysis it was proven that there was a significant difference in the onset of diarrhea with clean water sources for bathing / washing and community groups based on income. Diarrhea causes loss of work time resulting in a decrease in productivity. The average lost workday is 3.7 days with a loss of productivity losses of Rp1,041,400 obtained by dividing Surabaya's GDP estimates in 2014 with the workforce. Based on the prevalence of diarrhea 1.2%, the total loss due to poor access to clean water for bathing / washing in Surabaya's GDP is known at Rp1,640,003,100,000.